Teaching English as a foreign language through Merdeka curriculum framework: The four C’s (Critical thinking, Communication Collaboration, and Creativity) - Arum, Vindi Puspita; Ifrianti, Syofnidah; Puspita, Nurul (Journal of English Language Teaching and Learning (JETLE), 2025)
21st-century skills—critical thinking, communication, collaboration, and creativity—commonly known as the Four C’s, are essential for preparing students to thrive in modern educational and professional environments. This research was conducted in response to widespread confusion among teachers regarding the implementation of the Merdeka curriculum in Indonesian high schools. The study aimed to analyze how the Four C’s are incorporated into English language instruction under the Merdeka curriculum and to examine the extent to which these skills are integrated into the teaching modules. A qualitative research design was employed, utilizing documentation, observation, and interviews as data collection techniques. The presence of the Four C’s in teaching activities and instructional materials. Data analysis followed a three-stage process: data condensation, data display, and conclusion drawing. The findings offer insights into how the Four C’s are embedded in classroom practices and curriculum resources, and highlight challenges and opportunities for effective implementation.